2015
DOI: 10.1016/j.devcel.2015.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Irf4 Regulates the Choice between T Lymphoid-Primed Progenitor and Myeloid Lineage Fates during Embryogenesis

Abstract: T lymphoid-primed progenitors are hematopoietic progenitors destined to enter the thymus. The in vivo characterization of these embryonic progenitors is challenging, however, due to the intrauterine development of mouse embryos. Thus, how the fate of these cells is determined has not been fully defined in mammals. Here we use zebrafish embryos to show that the homing of T lymphoid-primed progenitors to the thymus is impaired, concomitant with a decrease in ccr9a expression, in the absence of irf4a. Strikingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…At the molecular level, analysis of gene-expression changes in HSPCs and ChIP-seq studies in human leukemia cell lines revealed a pleiotropic role for KDM2B in differentiation, quiescence, and lymphoid lineage specification through modulation of NOTCH, WNT, and interferon signaling; the latter not only regulates antiviral responses, but also plays important roles in lymphoid commitment and maturation of T cells (35,36). We discovered that KDM2B sustains NOTCH signaling in HSPCs and T-ALL, a leukemia known to harbor constitutive NOTCH activation (59).…”
Section: Methodsmentioning
confidence: 99%
“…At the molecular level, analysis of gene-expression changes in HSPCs and ChIP-seq studies in human leukemia cell lines revealed a pleiotropic role for KDM2B in differentiation, quiescence, and lymphoid lineage specification through modulation of NOTCH, WNT, and interferon signaling; the latter not only regulates antiviral responses, but also plays important roles in lymphoid commitment and maturation of T cells (35,36). We discovered that KDM2B sustains NOTCH signaling in HSPCs and T-ALL, a leukemia known to harbor constitutive NOTCH activation (59).…”
Section: Methodsmentioning
confidence: 99%
“…We observed developmental defects in blood islands and abnormal blood circulation after TNT exposure using state-of-the-art microscopy, and molecular analysis using real time PCR revealed decrease in the expression of gata1, an erythroid-specific transcription factor. gata1 is a master regulator in erythrocyte development and its expression labels erythroid lineage in hematopoiesis during zebrafish embryonic development [40,41]. Our data suggest that the in vivo toxicity of environmental polutants such as TNT can be assessed using the zebrafish hematopoietic and vascular systems and can be confirmed quantitatively by both imaging and molecular analyses.…”
Section: Discussionmentioning
confidence: 77%
“…The qPCR analysis was performed on an CFX96 Real-Time PCR system (Bio-Rad) using IQ SYBR Green Supermix (Bio-Rad) as described in the manufacture’s protocol. qPCR primers for nkx2.5 and amhc genes were synthesized and used as previously described [39] and gata1 primers as previously shown [41]. Each mRNA level was normalized to β-actin mRNA and then normalized to that of the control group.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, genes in the signaling pathways active in immune cell lineages were downregulated in Hira-KO cells, such as Irf4, Stat4, and rel. For example, IRF4 is required for development of both T and B lymphocytes (Biswas et al, 2012;Wang et al, 2015). Because transcription factors and signaling pathways influence many downstream target genes, their deficiency would cause an amplifying impact on gene expression.…”
Section: Discussionmentioning
confidence: 99%